Changes in muscle directional tuning parallel feedforward adaptation to a visuomotor rotation - de Rugy, Aymar; Carroll, Timothy J (Experimental brain research, 2010)
When people learn to reach in a novel sensorimotor environment, there are changes in the muscle activity required to achieve task goals. Here, we assessed the time course of changes in muscle directional tuning during acquisition of a new mapping between visual information and isometric force production in the absence of feedback-based error corrections. We also measured the influence of visuomotor adaptation on corticospinal excitability, to test whether any changes in muscle directional tuning are associated with adaptations in the final output components of the sensorimotor control system. Nine right-handed subjects performed a ballistic, center-out isometric target acquisition task with the right wrist (16 targets spaced every 22.5° in the joint space). Surface electromyography was recorded from four major wrist muscles, and motor evoked potentials induced by transcranial magnetic stimulation were measured at baseline, after task execution in the absence of the rotation (A1), after adaptation to the rotation (B), and after a final block of trials without rotation (A2). Changes in the directional tuning of muscles closely matched the rotation of the directional error in force, indicating that the functional contribution of muscles remained consistent over the adaptation period. In contrast to previous motor learning studies, we found only minor changes in the amount of muscular activity and no increase in corticospinal excitability. These results suggest that increased muscle co-activation occurs only when the dynamics of the limb are perturbed and/or that online error corrections or altered force requirements are necessary to elicit a component of the adaptation in the final steps of the transformation between motor goal and muscle activation.